STATE OF IMMUNE SYSTEM IN PATIENTS WITH PRIMARY HEADACHES - M. I. Karpova; A. S. Simbirtsev; Yu. S. Shamurov (Медицинская иммунология)
High incidence of accompanying somatic diseases has been revealed in patients with primary headache syndromes, while clinical manifestations of immune disorders being quite prevalent among them. The most common immune pathology in the studied patients were secondary immune deficiency and allergic diseases. Significant differences in the rates of chronic inflammatory and allergic diseases in patients with episodic and chronic primary headaches allow of considering these conditions as a factor unfavorably affecting clinical course of cephalalgias. The results of laboratory examinations in the studied patients showed presence of immune deficiency features, with changing ratio of immune subpopulations, altered functional activity of neutrophils, decreased IgG levels, and imbalance in cytokine system.